PERANAN SEKTOR INDUSTRI PENGOLAHAN TERHADAP PEREKONOMIAN DAN PENYERAPAN TENAGA KERJA DI PROVINSI SULAWESI UTARA - Ayu A. Amin; Grace A.J. Rumagit; Theodora M. Katiandagho (Universitas Sam Ratulangi, 2015)
ABSTRACT Ayu Azhari Amin. Role of Manufacturing Sector on the Economy and Labor Absorption in North Sulawesi (under the guidance of Grace A.J. Rumagit as chairman, and Theodora M. Katiandagho as a member). This study aimed to analyze the role of the manufacturing sector to the economy and employment in the province of North Sulawesi. This research was conducted for three months from February 2015 to April 2015 in the province of North Sulawesi, the data used in this research is secondary data obtained from the Central Bureau of Statistics North Sulawesi. This analysis using Location Quotient (LQ), Multiplier Share (MS), and the elasticity of labor, using variabe GDP and total employment. These results indicate that the role of the manufacturing sector to the economy in North Sulawesi are relatively stable from year to year, and in terms of the manufacturing sector GDP including the non bases. For that, we need further research to determine the factors forming GDP besides labor, which could boost the manufacturing sector GDP. Meanwhile, the role of the manufacturing sector on employment in the province of North Sulawesi is still relatively small and tend to be stable each year. Seen from the aspect of employment, including the processing industry sector basis. Keyword : Processing Industry Sector, Location Quotient, Multiplier Share, Elasticy Of Labor